6(x-1)=2(x-1)

Simple and best practice solution for 6(x-1)=2(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-1)=2(x-1) equation:



6(x-1)=2(x-1)
We move all terms to the left:
6(x-1)-(2(x-1))=0
We multiply parentheses
6x-(2(x-1))-6=0
We calculate terms in parentheses: -(2(x-1)), so:
2(x-1)
We multiply parentheses
2x-2
Back to the equation:
-(2x-2)
We get rid of parentheses
6x-2x+2-6=0
We add all the numbers together, and all the variables
4x-4=0
We move all terms containing x to the left, all other terms to the right
4x=4
x=4/4
x=1

See similar equations:

| 500=2500*0.04*t | | X+16y-34=0 | | 40-x=65-2x | | 2.8=z-6.3 | | (1÷6x)+(1÷12x)+(1÷7x)+5+(1÷2x)+4=5x | | (1÷6x)+(1÷12x)+(1÷7x)+5+(1÷2x)+4=x | | 2000=2000*8*r | | 4u-40=8(u-1) | | 1÷6x+1÷12x+1÷7x+5+1÷2x+4=x | | 2(y+8)=-2y+32 | | 2w-42=-4(w+6) | | 2w-42=4(w+6) | | 5(u+2)=-6u-45 | | 34=-5u+3(u+8) | | 20y+10(70-y)=1100 | | 2(v-8)-6v=16 | | -21=7w+8(w+3) | | 1800=10000*r*4 | | 12n+2-3n=7n | | 5x-x=2x^2 | | 500=p*0.08*2 | | 2x+.5x=68 | | 1j+3=7.2 | | 8x-5=25+10 | | 3n^2+10n-2=0 | | p²=−13p−36 | | p2=−13p−36 | | 15/38=b/19 | | 2(5x+3)=7x-9 | | 2(5x3)=7x-9 | | 15d=8 | | 5x+13x=73 |

Equations solver categories